Implementation of business logic for Legato Sapient (2021)
ABSTRACT: This project suggested the need to provide implementations which could be adapted to the customer requirements; Those implementations were based on business logics proposed by the customer. The integration of new business logics into the project contributed that the services provided by MES (Manufacturing Execution System) Legato Sapient could be adapted to the customer needs in a better way. In addition to the above, it was required to evaluate the new releases of Legato Sapient to detect bugs, ensuring that the bugs levels could remain as low as possible during the execution in the production environments. The implementations within the project ware divided into two sections, the first of them was the development of custom scripts, the purposes of these scrips sought an optimal way to extend existing functionalities, which have been created by the core team. The implemented scripts were: Configuration templates, Jobs, Data sources, KPIs (Key performance Indicators), Jobs, High charts. The second implementation was the Front-End development; for this purpose, the Framework Ember JS was used. Within the components developed with Ember JS are: custom-style-cellhourlyoutput-component and custom-style-crosstable-component. Those components improved the users experience when they worked with a boardlet based on a super generic table. Another critical aspect during the project was the testing phase, through this activity both bugs and incorrect parametrizations were found and fixed in the new releases of Legato Sapient, avoiding future reprocesses and customer complaints. The trace of the problems found were registered on Jira, which is one of the tools used for this project. Finally, the documentation supported each development, technical aspects were explained in detail.